Does board capital enhance corporate social responsibility disclosure quality? The role of CEO power. - Maswadi, Laila; Amran, Azlan (universiti sains malaysia, 2022)
This paper examines the relationship between board capital attributes and corporate social responsibility disclosure (CSRD) quality and how CEO power moderates the association between board capital attributes and CSRD quality. Using a cross-sectional sample of 114 firms, we find that directors' experience and directors' interlocking have positive impacts on CSRD quality while directors' political ties have a significant negative impact on CSRD quality in Saudi firms. Contrary to our hypotheses, we find no support for the impacts of directors' education, directors' expertise, and board nationality on CSRD quality. Moreover, we find partial support for the moderation effects of CEO power. Overall, we theoretically highlight the roles of resource dependence theory and agency theory in enhancing CSRD quality.